From objects to diagrams for ranges of functors - Gillibert, Pierre (Lecture notes in mathematics, 2011)
This work introduces tools from the field of category theory that make it possible to tackle a number of representation problems that have remained unsolvable to date (e.g. the determination of the range of a given functor). The basic idea is: if a functor lifts many objects, then it also lifts many (poset-indexed) diagrams.